2014
DOI: 10.1113/jphysiol.2013.270256
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training, but not resveratrol, improves metabolic and inflammatory status in skeletal muscle of aged men

Abstract: Key pointsr Ageing is associated with lifestyle-related metabolic diseases, and exercise training has been suggested to counteract such metabolic deteriorations.r The natural antioxidant resveratrol has been reported to exert 'exercise-like' health beneficial metabolic and anti-inflammatory effects in rodents, but little is known about the metabolic effects of resveratrol supplementation alone and in combination with exercise training in humans.r The present findings showed that exercise training markedly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 76 publications
(205 reference statements)
3
115
1
Order By: Relevance
“…(2014) recently showed that resveratrol supplementation also blunted training-induced decreases in protein carbonylation and tumour necrosis factor α (TNFα) mRNA within older individuals' skeletal muscle [178]. Thus, there are clear discrepancies between cell, rodent and human studies investigating resveratrol supplementation and it is currently unclear as to why resveratrol supplementation may display a negative effect on whole body/skeletal muscle adaptation when combined with endurance-exercise training in healthy individuals.…”
Section: Nicotinamide Riboside (Nr)mentioning
confidence: 99%
“…(2014) recently showed that resveratrol supplementation also blunted training-induced decreases in protein carbonylation and tumour necrosis factor α (TNFα) mRNA within older individuals' skeletal muscle [178]. Thus, there are clear discrepancies between cell, rodent and human studies investigating resveratrol supplementation and it is currently unclear as to why resveratrol supplementation may display a negative effect on whole body/skeletal muscle adaptation when combined with endurance-exercise training in healthy individuals.…”
Section: Nicotinamide Riboside (Nr)mentioning
confidence: 99%
“…By comparison, for example, of 855 enrolled participants in the HERITAGE study,8 652 had complete data; that is, the rate of missing data was 23.7%. Reports of other trials, many of them smaller, also report equivalent or higher rates of missing data68, 69, 70 or fail to report them at all 18, 71, 72, 73, 74. These studies suggest that the rate of missing data in our trial was typical for exercise training trials.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies in humans, by contrast, suggest that in aged, but healthy individuals RV blunts the positive cardiovascular effects of physical exercise (Gliemann et al, 2014(Gliemann et al, , 2013Olesen et al, 2014b). When submitted to eight weeks of high intensity training and a daily intake of either 250 mg of RV or placebo, the subjects that received RV showed no increase in the capillary-to-fiber ratio or the concentration of vascular endothelial growth factor in the vastus lateralis.…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…On the other hand, enough evidence has been gathered to suggest that compromised populations such as the elderly do benefit from treatment with RV (Smoliga et al, 2013). Even though a recent series of publications in aged humans (Gliemann et al, 2014(Gliemann et al, , 2013Olesen et al, 2014b) reveals no benefit from RV supplementation in a broad range of cardiovascular and metabolic parameters, further research needs to be conducted to definitely validate the claims both in favor and against RV.…”
Section: Perspectivementioning
confidence: 99%